2006
DOI: 10.1007/s11248-006-0004-5
|View full text |Cite
|
Sign up to set email alerts
|

Production of Transgenic-clone Pigs by the Combination of ICSI-mediated Gene Transfer with Somatic Cell Nuclear Transfer

Abstract: The objective of this study was to examine whether the ICSI-mediated gene transfer method using in vitro matured oocytes and frozen sperm head could actually produce transgenic pigs. We also aimed at examining whether transgenic pigs can be cloned from somatic cells of a transgenic pig generated by the ICSI-mediated method. A bicistronic gene constituted of the human albumin (hALB) and enhanced green fluorescent protein (EGFP) genes was introduced into pig oocytes by the ICSI-mediated method. Transfer of 702 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 33 publications
5
66
1
Order By: Relevance
“…The overall production efficiency of the cloned piglets was 3.1% from the recipients that farrowed or received a Caesarian section (17/547). Cloning efficiency of GalT-KO pigs in these experiments was comparable to that of non-KO pigs that we had reported previously (Kurome et al, 2006;Matsunari et al, 2008b).…”
Section: Creation Of Cloned Pigs From Galt-ko Cellssupporting
confidence: 84%
“…The overall production efficiency of the cloned piglets was 3.1% from the recipients that farrowed or received a Caesarian section (17/547). Cloning efficiency of GalT-KO pigs in these experiments was comparable to that of non-KO pigs that we had reported previously (Kurome et al, 2006;Matsunari et al, 2008b).…”
Section: Creation Of Cloned Pigs From Galt-ko Cellssupporting
confidence: 84%
“…The use of pig kidney fibroblasts as donor cells for SCNT experiment has been reported by several investigators [8,10,37]. However, to our knowledge, we produced the first cloned miniature piglet derived from kidney cells of an aged adult.…”
Section: Discussionmentioning
confidence: 98%
“…To date, pigs have been produced by SCNT techniques using donor cells derived from fetuses and young pigs [4][5][6][7][8][9][10][11][12][13]. The use of pig kidney fibroblasts as donor cells for SCNT experiment has been reported by several investigators [8,10,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Damage to the sperm plasma membranes causes DNA to associate with important consequences for the transfer of DNA into oocytes (Perry et al 1999). However, sperm pretreatments that markedly disrupt the plasma membrane cause DNA fragmentation (Szczygiel et al 2003), or can damage the sperm nucleus and lead to lower efficiency of embryogenesis following ICSI (Kurome et al 2006, García-Vázquez et al 2009). It is also commonly found that transgenes integrated by passive transgenesis commonly form long concatameric arrays .…”
Section: F a García-vázquez And Othersmentioning
confidence: 99%